Social Panorama of Latin America 2008 - United Nations (United Nations, 2010)
A constant in the Social Panorama of Latin America is the chapter on poverty dynamics in Latin America. The 2008 edition is no exception. Up-to-date estimates and analyses of the relevant figures, based on household surveys conducted in 18 countries, are provided for the year 2007. Three other chapters focus on the specific topics of the new employment-related target which has been incorporated into the Millennium Development Goals, the demographic dividend as an opportunity for expanding secondary education coverage, and the issue of youth violence and family violence as viewed from a perspective of social inclusion.